Application of multiomics analysis to plant flooding response - Gui, Guangya; Zhang, Qi; Hu, Weiming; Liu, Fen (Frontiers in Plant Science, 2024)
Flooding, as a natural disaster, plays a pivotal role in constraining the growth and development of plants. Flooding stress, including submergence and waterlogging, not only induces oxygen, light, and nutrient deprivation, but also alters soil properties through prolonged inundation, further impeding plant growth and development. However, hypoxia (or anoxia) is the most serious and direct damage to plants caused by flooding. Moreover, flooding disrupts the structural integrity of plant cell walls and compromises endoplasmic reticulum functionality, while hindering nutrient absorption and shifting metabolic processes from normal aerobic respiration to anaerobic respi-ration. It can be asserted that flooding exerts comprehensive effects on plants encompassing phenotypic changes, transcriptional alterations, protein dynamics, and metabolic shifts. To adapt to flooding environments, plants employ corresponding adaptive mechanisms at the phenotypic level while modulating transcriptomic profiles, proteomic characteristics, and metabolite levels. Hence, this study provides a comprehensive analysis of transcriptomic, proteomic, and metabo-lomics investigations conducted on flooding stress on model plants and major crops, elucidating their response mechanisms from diverse omics perspectives.